ANALISIS PRESTASI KERJA PEGAWAI NEGERI SIPIL FAKULTAS HUKUM UNIVERSITAS TADULAKO PROPINSI SULAWESI TENGAH - Haeruddin, Haeruddin (Katalogis, 2015)
The problem in this research is how the performance of Civil Servants in the Law Faculty of the University of Central Sulawesi Tadulako, informants in this study were employees at the Faculty of Law Unersitas Tadulako Central Sulawesi purposife determined by sampling techniques. Retrieval techniques and data collection consists of observation, interviews and documents. Technical analysis of the data include data reduction, presentation and withdrawal pesimpulan. The theory of performance used in this research is the theory of Cost and James (2002: 25) include the ability (ability) effort (effort), and opportunity (chance). Formulation of the problem in this research is how the performance of Civil Servants in the Law Faculty of the University of Central Sulawesi Tadulako, informants in this study were employees at the Faculty of Law Unersitas Tadulako Central Sulawesi purposife determined by sampling techniques. Retrieval techniques and data collection consists of observation, interviews and documents. Technical analysis of the data include data reduction, presentation and withdrawal pesimpulan. The theory of performance used in this research is the theory of Cost and James (2002: 25) include the ability (ability) effort (effort), and opportunity (chance).